Phenomenology, epidemiology, co-morbidity and treatment of a specific phobia of vomiting: A systematic review of an understudied disorder. (March 2018) - Keyes, Alexandra; Gilpin, Helen R.; Veale, David
Abstract: Specific Phobia of Vomiting (SPOV) is an under-researched disorder compared to other Specific Phobias. A systematic review was conducted to synthesise existing research across areas of phenomenology, aetiology, epidemiology, co-morbidity, assessment measures and treatment. Online databases (Psychinfo, Embase, Medline, Pubmed and Cochrane Library) were searched using terms related to SPOV and 'emetophobia'. A manual search of reference lists of included papers was also conducted. In total, 385 articles were found and 24 were included in the review. The review was registered on the PROSPERO register (CRD42016046378). The review presents a qualitative synthesis of identified studies exploring the features of SPOV including locus of fear, feared consequences of vomiting, and common safety and avoidance behaviours. It also identified articles describing aetiological factors involved in the development of SPOV, co-morbid disorders and the epidemiology of the disorder. Further studies focused on valid and reliable measures to assess SPOV, and treatments that are effective at reducing symptomatology of SPOV and psychological distress. There are relatively few published research articles on SPOV, and particularly high quality studies exploring effective treatment options for SPOV. Further research should focus on RCTs for comparing different approaches to reducing symptomatology and distress in people with SPOV. Highlights: The first systematic review of existing literature on Specific Phobia of Vomiting Lack of research compared to other phobias, especially into effective interventions RCTs needed to evaluate effective treatments and comparison to other approaches.